Do Transportation Infrastructure Investments Reduce Inventory Levels in the Manufacturing Sector in China?. (July 2020) - Lin, Ya; Zhao, Quanwu; Liu, Peisen; Zhang, Qinhong
Based on provincial panel data observed over the 2005–2014 period, we analyze the impacts of transportation infrastructure investments on inventory levels in China's manufacturing sector. Our results indicate that transportation infrastructure investments do not reduce inventory levels in the manufacturing sector in China. This conclusion is different from the results in the previous literature, which demonstrate positive effects of transportation investments on reducing inventory levels. The difference can be partly explained by the ongoing inland shift of industry and geographic market expansion in China, which lead to longer transportation distances and longer lead times from suppliers to customers. We also find that road investments have spatial spillover effects overall, and the impacts of different types of road investments differ significantly from each other. Railway investments, however, do not have spatial spillover effects. Finally, we present several policy implications of transportation infrastructure investments, inland shifts of industry, and geographic market expansion.